On CN-fibrations in bitopological semigroups - Dawood, Suliman; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
We extend the path lifting property in homotopy theory for topological spaces to bitopological semigroups and we show and prove its role in the CN-fibration property. We give and prove the relationship between the CN-fibration property and an approximate fibration property. Furthermore, we study the pullback maps for CN-fibrations.